MARINE BIO-NANOTECHNOLOGY SILVER (AgNPs) OF MANGROVE EXTRACT AND ITS APLICATION : A REVIEW - Willian, Nancy (Jurnal Zarah, 2018)
The synthesis of nanoparticles (NP) using marine plants has been well developed. In recent years, few reports of NP synthesis use mangroves, which are used as bio plants for synthesis. In addition, mangroves are a renewable, sustainable and economical source compared to other marine organisms, so they can be explored effectively in the synthesis of green NPs (Green Synthesis). Therefore, this study reports on the biosynthesis of NP, especially silver nanoparticles (AgNPs) using mangrove extracts. NPs synthesized by this method are primarily spherical with promising anti-microbial potential. The biosynthesis of silver nanoparticles can be triggered by several compounds such as carbonyl, terpenoid, phenolic, tannin, flavonone, amine, amide, protein, pigment, alkaloid and other reducing agents in biological extracts capable of as reducing agents and capping agents. Marine bio-nanotechnology has great promise in nanomedicines, groceries, pharmaceuticals and industrial fabrics for the future.